International business - Dlabay, Les R.; Scott, James Calvert (Cengage Learning Asia Pte Lte, 2012)
This book provides the foundation for studying international business and conducting business in today's global environment. Students develop the appreciation, knowledge, skills and abilities to live and work in a global marketplace.